Integrated Management of a Large Radicular Cyst: A Case Report on Efficacy of Decompression and Conservative Approaches - Ali Chamani; Siavash Moushekhian; Mina Zarei; Reza Shakiba; Mohammad Hossein Davarian (Clinical Case Reports)
ABSTRACT The decompression technique can effectively reduce the size of large periapical lesions, minimize tissue damage, and enhance surgical outcomes. This conservative approach allows for better management of extensive lesions, potentially improving patient recovery and decreasing the need for more invasive procedures.